Price Dynamics in China. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Chinese inflation, particularly non-food inflation, has been surprisingly modest in recent years. We find that supply factors, including those captured through upstream foreign commodity and producer prices, have been important drivers of non-food inflation, as has foreign demand for Chinese goods. Domestic demand and monetary conditions seem less important, possibly reflecting a large domestic output gap generated by many years of high investment. Inflation varies systemically within China, with richer (and urban) provinces having lower, more stable, inflation, but this urban inflation also influence that in lower-income provinces. Higher Mainland food inflation also raises inflation in non-Mainland China.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet